Experimental Investigation of Mass Transfer for Copper Reduction by Weight Difference Technique - Ibrahim, Marwa H.; Najim, Sarmad T. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
An experimental analysis was included to study and investigate the mass transport behavior of cupric ions reduction as the main reaction in the presence of 0.5M H2SO4 by weight difference technique (WDT). The experiments were carried out by electrochemical cell with a rotating cylinder electrode as cathode. The impacts of different operating conditions on mass transfer coefficient were analyzed such as rotation speeds 100-500 rpm, electrolyte temperatures 30-60 , and cupric ions concentration 250-750 ppm. The order of copper reduction reaction was investigated and it shows a first order reaction behavior. The mass transfer coefficient for the described system was correlated with the aid of dimensionless groups as follows: Sh = 3.77 4075 < Re < 34088